Globalisation and governance in India: some thoughts - Singh, Surjit (2003)
This paper looks at the political stability issues for India in the face of increasing Globalisation. It is discussed that there is no doubt that Indian economy has observed positive changes over time, but under the new globalized regime, the vlnerability has increased which has implications for political stability of the country. We must learn lessons from East Asian crisis. In the past, India has largely managed to evade the main impact of the South East Asian financial crisis, but if we accept the irrationality hypothesis, then of course "anything is possible." - Reproduced.
Keywords: Globalization - India; Globalization